2021
DOI: 10.1186/s12889-021-10973-9
|View full text |Cite
|
Sign up to set email alerts
|

Motivating antibiotic stewardship in Bangladesh: identifying audiences and target behaviours using the behaviour change wheel

Abstract: Background South Asia is a hotspot for antimicrobial resistance due largely to over-the-counter antibiotic sales for humans and animals and from a lack of policy compliance among healthcare providers. Additionally, there is high population density and high infectious disease burden. This paper describes the development of social and behavioural change communication (SBCC) to increase the appropriate use of antibiotics. Methods We used formative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…However, another study found that institutional training provided to medical students might not effectively raise sufficient awareness [ 38 ]. In a 2021 study [ 39 ], experts suggested that improving awareness and practices, primarily among households and pharmacy shopkeepers, are expected to bring the highest impact, secondary to targeting behaviors of physicians and pharmaceutical companies.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study found that institutional training provided to medical students might not effectively raise sufficient awareness [ 38 ]. In a 2021 study [ 39 ], experts suggested that improving awareness and practices, primarily among households and pharmacy shopkeepers, are expected to bring the highest impact, secondary to targeting behaviors of physicians and pharmaceutical companies.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside, this instigates antimicrobial stewardship programs (ASPs) in ambulatory care similar to other important antibiotics in Bangladesh where there are concerns about resistance development [107][108][109][110]. This includes ASPs among community pharmacists and drug sellers building on ASPs in other sectors in Bangladesh [52,111].…”
Section: Discussionmentioning
confidence: 99%
“…This is important in Bangladesh, given extensive colistin-resistant Escherichia coli in broiler meat and chicken feces [44][45][46], exacerbating resistance among patients to colistin in Bangladesh [47][48][49][50]. Over-the-counter dispensing of antibiotics is also common in Bangladesh and a concern, especially when this involves 'Watch' and 'Reserve' antibiotics [51][52][53][54] Overall, activities to enhance the appropriate use of colistin in both animals and humans are essential as colistin still remains the antibiotic of choice for multiple drug-resistant gram-negative bacterial infections (MDR-GNB). This includes carbapenem-resistant Acinetobacter baumannii (CRAB) as well as other pathogens resistant to the new antimicrobial agents [55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the misuse and overuse of antibiotics are two major causes contributing to the development of antibiotic-resistant pathogens [ 13 ]. Bangladesh, as a densely populated country with a high burden of infectious diseases, faces substantial challenges in managing AMR [ 14 ]. All the main factors contributing to the emergence of AMR in Bangladesh can be categorized into the supply and demand sides.…”
Section: Introductionmentioning
confidence: 99%